Dari Politik Simbolik ke Politik Substansial dalam Kebijakan Pendidikan Islam Kontemporer - Dudi Ismail; Risa Apriani; Nelis Lestari SM; Iit Supriatin (PT. Student RIhlah Indonesia, 2026)
Islamic education policies in Indonesia over the past two decades have increasingly employed Islamic symbols within regulations and educational programs; however, these symbolic representations are not always accompanied by substantive transformations in epistemological orientation, curriculum design, and educational outcomes. This condition highlights the urgency of examining the relationship between symbolic politics and substantive politics in contemporary Islamic education policy. This study aims to analyze the patterns of symbolic politics in Islamic education policies, assess the degree of policy substantiveness, and propose a transition model toward more substantive policy frameworks. Employing a qualitative approach, this research utilizes library research and document analysis of Islamic education policies issued between 2014 and 2026. The analysis integrates Murray Edelman’s theory of symbolic politics with the maqāṣid al-sharī‘ah framework. The findings reveal that Islamic education policies remain predominantly symbolic, emphasizing normative legitimacy and administrative compliance, while substantively transformative policies remain limited and unevenly implemented. This article contributes a novel integrative analytical framework combining symbolic politics and maqāṣid al-sharī‘ah, along with a substantive policy transformation model. The findings imply that Islamic education policymaking must shift toward substantively oriented strategies that prioritize educational quality, institutional governance, and measurable learning outcomes.